Spinal Anesthesia for Emergent Abdominal Surgery in a Patient With a Tricuspid Valvectomy: A Case Report. Issue 7 (1st April 2018) - Harold, Katherine Henderson; Webster, Michael
Abstract : Tricuspid valvectomy without replacement is an accepted treatment for drug-resistant endocarditis. The current intravenous drug abuse epidemic is leading to more occurrences of right-sided valvular endocarditis. This suggests that the incidence of tricuspid valvectomies may rise. Our academic hospital has seen 3 such patients in the past year alone. We review the implications of this pathophysiology and discuss the anesthetic management of a 33-year-old woman with previous tricuspid valvectomy presenting for emergent abdominal surgery.